Reconfigurable manufacturing systems characteristics in digital twin context - Tang, Jiecheng; Emmanouilidis, Christos; Salonitis, Konstantinos (Elsevier, 2021)
The concept of a reconfigurable manufacturing system (RMS) has been introduced to enable production systems to continuously evolve and respond rapidly to unpredicted and fluctuating market environments. To achieve this goal, RMS needs to exhibit six core characteristics: modularity, integrability, scalability, diagnosability, convertibility and customisation. These characteristics are required to ensure manufacturing systems’ resilience while maintaining productivity and quality. Assessing these characteristics at both the design and operating phase can be aided by the digital twinning (DT) of physical systems. To this end, the DT-RMS concept is introduced in this paper as a dynamic cyber-replica of the physical production environment, enabling a high-level of transparency about data, performance, and relevant reconfiguration decisions. As a result, DT-RMS responds to the need to integrate requirements and performance targets for the RMS characteristics at design and operating-time
Keywords: Digital Twins; Reconfigurable Manufacturing Systems; System architecture